Cartographer - Preetom, Istefan Islam; Shovon, Tanvir Ahmed; Mahmud, Tahsin (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2010.